GCTOF-MS Combined LC-QTRAP-MS/MS Reveals Metabolic Difference Between Osteoarthritis and Osteoporotic Osteoarthritis and the Intervention Effect of Erxian Decoction - Ma, Zhenyuan; Wei, Yibao; Zhang, Li; Shi, Xiaoqing; Xing, Runlin; Liao, Taiyang; Yang, Nan; Li, Xiaochen; Jie, Lishi; Wang, Peimin (Frontiers in Endocrinology, 2022)
Purpose:OP and OA are chronic bone diseases with high incidence in the middle-aged and elderly populations.The latest study shows that the latest research shows that the pathological environment of OP may be involved in the aggravation of the pathological process of OA,and the pathological state of OP plays an important role in the aggravation of OA pathology.EXD is a traditional Chinese medicine decoction,has been used to treat osteoporosis.Therefore, we further study whether OA will be aggravated in the OP environment,and whether EXD can alleviate OA by intervening in the OP environment.The purpose of this study was to analyze the effect of OP on OA metabolites by using metabolomic method and to explore the intervention mechanism of EXD on osteoporotic OA.Method:Thirty-two SD rats were randomly divided into Normal group,OAgroup,OP-OAgroup and EXD group.EXD was administered by gavage.Histopathological evaluation of cartilage tissue was performed using Saffron fast green and HE staining.Western blot and qRT-PCR were used to detect the expression levels of chondrogenesis genes SOX9,COL2A1 and COMP in cartilage tissue.GC-TOFMS and LC-QTRAP-MS/MS metabolomics methods were used to analyze the changes of metabolites in serum samples of rats in each group.Result:The slice results showed that the cartilage damage in the OP-OA group was more serious than that in the OA group,which was significantly relieved after EXD intervention.The results confirmed that the cartilage damage in the OP-OA group was more severe than that in the OA group and further reduced the protein and gene expressions of cartilage markers SOX9,COL2A1,and COMP.Thirty-seven substances were identified,and Gentiopicroside,Emodin,Quercetin,Diosmetin were analyzed as possible active components of EXD.EXD treatment significantly reduced cartilage damage and reversed the expression of these markers.Metabolomics showed that EXD attenuated cartilage destruction by modulating the expression of cystine,chenodeoxycholate and D-Turanose,involving glycolysis/gluconeogenesis, pantothenate and CoA biosynthesis metabolic pathways. Conclusion:The OP environment may promote the progression of OA through metabolic factors.Benign intervention of EXD in osteoporotic OA involves cystine, chenodeoxycholate and D-Turanose,and their associated glycolysis/gluconeogenesis,pantothenate and CoA biosynthesis metabolic pathways.Therefore,we have a deep understanding of the metabolic-related intervention of EXD in osteoporotic OA,and are eager to better understand the mechanism of multi-targeted intervention of EXD in bone metabolic lesions.